Explaining Spatial Patterns of Foreign Employment in Germany - Robert Lehmann; Wolfgang Nagl (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper investigates the main determinants of the regional representation of foreign employees in Germany. Since migration determinants are not necessarily the same for workers of different nationalities, we explain spatial patterns not only for total foreign employment but also for the 35 most important migration countries to Germany. Based on a total census for all 402 districts in Germany, we find a large heterogeneity in migration determinants between nationalities. We identify three groups of countries for which labor market and economic conditions, amenities or cultural factors are more important. Geographical distance plays a major role in location decisions, a finding that is especially pronounced for workers from countries neighboring Germany.
Keywords: F22; J21; J61; O15; R12; 330; foreign employment; migration determinants; distance; spatial models